Alterations in Muscle Force Control With Aging: Is There a Modulatory Effect of Lifelong Physical Activity? - Pethick, Jamie; Piasecki, Mathew (Frontiers in Sports and Active Living, 2022)
Recent technological developments have enabled significant advances in our understanding of the ability to voluntarily control muscle force output. The fluctuations inherent to muscle force output can be quantified according to both their magnitude and temporal structure (or “complexity”), with such quantification facilitating comparison of force control between distinct populations. In comparison to young adults, older adults exhibit an increase in the magnitude (i.e., decreased steadiness) and a decrease in the complexity (i.e., decreased adaptability) of force fluctuations, both of which are indicative of a loss of force control. There remain, however, key gaps in knowledge that limit our interpretation of this age-related loss of force control. One such gap relates to the effect of lifelong physical activity on force control. To date, research on aging and force control has largely been conducted on inactive or moderately active older adults. However, high levels of lifelong physical activity, such as that exhibited by Masters athletes, have been shown to have protective effects on the function and morphology of the neuromuscular system. Some of these effects (e.g., on impaired inhibitory transmission in the motor cortex and on motor unit discharge rates) have the potential to attenuate the age-related loss of force control, while others (e.g., greater motor unit remodeling capacity) have the potential to worsen it. We therefore propose that, in order to progress our knowledge of the effects of aging on force control, future studies must consider the potential modulatory effect of lifelong physical activity.